DNA barcoding unveiling rare species: the case of Pruvotfolia pselliotes (Labbé, 1923) (Mollusca: Gastropoda: Nudibranchia) in the Mediterranean Sea - G. Furfaro; G. Chimienti; P. Mariottini (The European Zoological Journal, 2020)
The Mediterranean Sea is a hot spot for marine biodiversity, and this is particularly evident taking into consideration the diversity observed in many animal groups, among them the Molluscs. In the last decade, several works have revealed a high rate of cryptic diversity characterizing the Molluscan fauna of the Mediterranean Sea and an increasing number of endemic and/or new species inhabiting this semi-enclosed basin have been recorded or described. The DNA-barcoding method is considered an essential step in the integrative taxonomy applications, to unravel cryptic diversity and for species identification. Here we report the case of DNA-barcoding technique applied to identify a nudibranch (Heterobranchia) collected from the Adriatic Sea, in the Bay of Kotor (Montenegro), for which a standard morphological identification was not possible. Mediterranean specimen belonging to Pruvotfolia pselliotes (Labbé, 1923) is for the first time molecularly identified and its COI DNA sequence compared with the one of an individual collected from the type locality. In addition, this is the first verified report of this species from the Adriatic Sea. Finally, the potential of using DNA-barcoding is here discussed, together with the habitat and the geographical distribution of this uncommon species.